RETRACTED: Valorization of Plastic Waste in the Manufacture of Paving Stones in Congo Republic: The Case of Polyethylene Terephthalates (PET) - Berry, Ulrich; Nkeletela, Laurette Brigelia; Samba, René Evrard Josué; Motoula, Smäel Magloire Elombo; Mikanou, Olivier Mabiala (Asian Journal of Science, Technology, Engineering, and Art, 2025)
This study addresses the challenge of plastic waste, one of the major contributors to environmental pollution by proposing its valorization through recycling for construction applications. Specifically, the research explores the use of waste thermoplastics, with emphasis on polyethylene terephthalate (PET) collected from the streets of Brazzaville, as a binder in the production of paving blocks for road surfacing. The methodology involved incorporating 53.33% recycled plastic into a sand matrix to form paving blocks, with performance evaluation focused on water absorption behavior. The results indicate that the paving blocks exhibit very low water absorption rates, which remain nearly constant despite variations in plastic content. These findings suggest that PET-based recycled composites have favorable properties for road surfacing, demonstrating both environmental and practical benefits. The study highlights the potential of such recycling approaches to reduce plastic pollution while contributing to sustainable infrastructure development.